Brunner & Suddarth's textbook of medical-surgical nursing - Brunner, Lilian Sholtis; Hinkle, Janice L.; Cheever, Kerry H. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"This textbook has been a favorite resource for students, instructors, and practicing nurses for almost a half-century. It's comprehensive yet accessible approach covers a broad scope of medical conditions while focusing strongly on the nurse's role in caring for, educating, and assisting patients and families"--Provided by publisher.
Machine generated contents note: Health Care Delivery and Evidence-Based Nursing Practice -- Community-Based Nursing Practice -- Critical Thinking, Ethical Decision Making and the Nursing Process -- Health Education and Promotion -- Adult Health and Nutritional Assessment -- Individual and Family Homeostasis, Stress, and Adaptation -- Overview of Transcultural Nursing -- Overview of Genetics and Genomics in Nursing -- Chronic Illness and Disability -- Principles and Practices of Rehabilitation -- Health Care of the Older Adult -- Pain Management -- Fluid and Electrolytes: Balance and Disturbance -- Shock and Multiple Organ Dysfunction Syndrome -- Oncology: Nursing Management in Cancer Care -- End-of-Life Care -- Preoperative Nursing Management -- Intraoperative Nursing Management -- Postoperative Nursing Management -- Assessment of Respiratory Function -- Respiratory Care Modalities -- Management of Patients With Upper Respiratory Tract Disorders -- Management of Patients With Chest and Lower Respiratory Tract Disorders.
Preceded by Brunner & Suddarth's textbook of medical-surgical nursing / Suzanne C. Smeltzer ... [et al.]. 12th ed. c2010.
Includes bibliographical references and index.
Nursing
Keywords: Nursing Care; Perioperative Nursing